Accounting Conservatism: Firm Size and Financial Distress - Permatasari, Maulina Dyah; Widiastuti; Yahya, Adibah; Rahmadaini, Ade (Owner : Riset dan Jurnal Akuntansi, 2024)
This study aims to investigate the effect of firm size and financial distress on accounting conservatism. Accounting conservatism is an approach in which earnings are recorded more conservatively or cautiously, with a tendency to recognise losses sooner than recognise gains. These factors can influence the practice of accounting conservatism in various ways. This study uses financial data from various companies in diverse industries and uses statistical methods to analyse the relationship between company size (both large and small) and level of financial distress with accounting conservatism practices. The results of this study are expected to provide a deeper understanding of the factors that influence accounting conservatism and how accounting practices may change in different situations of company size and financial distress. The type of research in this study is descriptive quantitative with descriptive statistical data analysis and classical assumption testing, hypothesis testing and coefficient of determination test. The results showed that partially and simultaneously company size and financial distress had no effect on accounting conservatism.